A comparison of the interaction of anthelmintic benzimidazoles with tubulin isolated from mammalian tissue and the parasitic nematode Ascaridia galli. - Dawson, P; Gutteridge, W; Gull, K (1984)
Colchicine and a range of anthelmintic benzimidazoles inhibited the in vitro polymerization of tubulin purified from the parasitic nematode Ascaridia galli. In most cases, this inhibition was more pronounced than that detected when these drugs were incubated with tubulin purified from mammalian tissue. In particular, oxfendazole and thiabendazole had virtually no effect on mammalian tubulin assembly whereas they were both good inhibitors of nematode tubulin polymerization. Electron microscopic examinations revealed no morphological differences between microtubules from either nematode or mammalian tissues polymerized in the presence or absence of drug, though the length and number of microtubules was reduced in the drug-incubated samples. These results show that the benzimidazole group of anthelmintics interacts specifically with nematode tubulin and that their selectivity, at least in part, is a direct consequence of such interaction.